Integrais de caminho na mecânica quântica e na teoria quântica de campos como base para as regras de Feynman - Lapola, Marcelo Montenegro [UNESP] (2016)
One of the alternative approaches used in quantum mechanics and quantum field theory, which takes the most advanced developments in the area, such as string theory, is to use the formalism of path-integrals . A path-integral is an efficient way to calculate scattering amplitudes of a transition from one quantum state to another. In this work are presented some essential ideas about the path-integrals, applications in ordinary quantum mechanics (nonrelativistic) and then to base the rules of Feynman for interactions between particles in quantum field theory, with some deductions to generating funcionals for scattering amplitudes in free field and in the presence of interactions fields